Pendidikan: Kunci Keadilan Sosial - Tunisa, Resti Latipa; Asbari, Masduki; Ahsyan, Diyaul; Utami, Ulan Rizki (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this discussion is to describe education in Indonesia as the key to social justice because quality and equitable education can open up equal opportunities for every individual to achieve prosperity and equal treatment. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from Anies Baswedan's YouTube channel entitled